Thickness Induced Line-Defect Reconfigurations in Thin Nematic Cell - M. Ambrožič; S. Kralj (Advances in Condensed Matter Physics)
We studied the impact of the cell thickness on configurations of line disclinations within a plane-parallel nematic cell. The Lebwohl-Lasher semimicroscopic approach was used and (meta)stable nematic configurations were calculated using Brownian molecular dynamics. Defect patterns were enforced topologically via boundary conditions. We imposed periodic circular nematic surface fields at each confining surface. The resulting structures exhibit line defects which either connect the facing plates or remain confined within the layers near confining plates. The first structure is stable in relatively thin cells and the latter one in thick cells. We focused on structures at the threshold regime where both structures compete. We demonstrated that “history” of samples could have strong impact on resulting nematic configurations.